THE INDONESIA-MIDDLE EAST BUSINESS CYCLE SYNCHRONIZATION - Agustiar, Memet (Fakultas Ekonomi dan Bisnis, UNTAN, 2023)
This study aims to analyze the business cycle synchronization (BCS) between Indonesia and 14 Middle Eastern countries and its determinants. The BCS was measured using BCS Index. The panel data was analysed using Feasible General Least Square with estimated coefficients. The results show that the Indonesia-Middle East BCS is strong in terms of index and trend. Trade openness positively and significantly affects the BCS. This study provides evidence for the endogeneity of trade relations and the BCS. Price factors, such as inflation and exchange rates, are more difficult to forecast. This information allows stakeholders to promote Indonesia